Upaya Guru Dalam Mengatasi Siswa Reterdasi Mental Di MI Muhammadiyah Mungkung Kalikajar: teacher efforts, mental retardation - Adib, Wildan; Ramadhani, Diva; Munawaroh, Hidayatu (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2023)
Mental retardation is a condition characterized by a child's intelligence that is below average unlike children in general which causes the child's inability to learn and adapt to the demands of society for normal abilities, generally mentally retarded children in participating in learning will be difficult to accept learning material. This study aims to determine how the teacher's efforts in overcoming mental retardation in students at MI Muhammadiyah Kalikajar. This research uses a qualitative descriptive method with research subjects including teachers in class IV and mentally retarded students at MI Muammadiyah Mungkung. Data collection using interview, observation and documentation techniques. Data analysis is known by using reduction, presentation and drawing conclusions. The results showed that the motivation, support and guidance provided by class teachers and subject teachers at MI Muhammadiyah Mungkung Kalikajar in overcoming students with mental retardation include 1) providing special attention in the form of motivational spirit and support, 2) providing individualized assistance when students experience difficulties, 3) providing additional material outside of learning hours, 4) involving active students in learning according to students' abilities.